Public History: Suatu Tinjauan Pendahuluan - Jumardi Jumardi (Jurnal Pendidikan Sejarah, 2015)
The low attention to learners, students and the public on the history as well as the withdrawal of the application of curriculum in 2013 add to the problems of strengthening the role of history in the nation’s character. This affects the poor students who want to pursue higher education studies for history or science education majors history, plus the lack of job security from the government. Government and stakeholders are obliged to fix the condition of the nation and state are already crisscrossing this. We need a breakthrough in learning activities or movements to public awareness that history is not solely belong to the ruling, but the history is the property of the entire nation of Indonesia. Public history is expected to be a breakthrough in the history closer to the people. Besides public history programs provide employment opportunities for graduates to be able to work in all areas of life, and not fixated on any one area of work. In the public program history, the public are invited to play an active role in the history of his people, so that the character of a nation is not just a slogan government alone